STUDI KOMPARATIF PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT. BPR. MERTHA SEDANA DAN PT. BPR. MAS GIRI WANGI - Dwi Divayana, Kadek Ari; Rahanatha, Gede Bayu (E-Jurnal Manajemen; Vol 7 No 4 (2018)DO - 10.24843/EJMUNUD.2018.v07.i04.p15, 2018)
This study aimed to compare the effect of service quality on customer satisfaction of PT. BPR. Mertha Sedana and PT. BPR. Mas Giri Wangi. The study involved 2 kinds of Bank which has similarities to the capital but both of them are located in different places. Multiple linear regression analysis was used as a data analysis technique. The sampling technique used in this research is purposive sampling. Purposive sampling is sampling with particular consideration to the criteria used in determining the final sample of at least high school education, customers of the relevant BPR and conduct a transaction on related BPR. The number of respondents involved in each - each BPR is 65 so that the total respondents involved is 130 people. Based on the results of hypothesis testing showed variable physical evidence, reliability, responsiveness, assurance and empathy effect on customer satisfaction variables both customers of PT. BPR. Mertha Sedana and PT. BPR. Mas Giri Wangi. Results are the quality of services consisting of physical evidence, reliability, responsiveness, assurance and empathy positive and significant impact on customer satisfaction in both of BPR. Empathy is the most dominant variable influence on customer satisfaction PT. BPR. Mertha Sedana, while reliability is the most dominant variable affecting customer satisfaction PT. BPR. Mas Giri Wangi.   Keywords: Bank Perkreditan Rakyat (BPR), Service quality, customer satisfaction.